Recent Advances in 1D Nanomaterial‐Based Bioelectronics for Healthcare Applications. Issue 3 (11th December 2021) - Song, Sangmin; Kim, Kyung Yeun; Lee, Sun Hee; Kim, Kyun Kyu; Lee, Kyungwoo; Lee, Wonryung; Jeon, Hojeong; Ko, Seung Hwan
Abstract : With the rapid development of wearable devices, healthcare technologies that enable an accurate monitoring of electrophysiological signals and provide electrical stimulation for therapy are extensively researched. In this regard, 1D nanomaterials are widely used in bioelectronics owing to their advantageous properties such as transparency, mechanical flexibility, and stretchability. Herein, the recent advances in bioelectronic devices based on 1D nanomaterials are reviewed with a focus on the biocompatibility of 1D nanomaterials frequently used in bioelectronic devices. In particular, bioelectronic devices used for recording and stimulating cell signals in in vitro environments, monitoring electrophysiological signals, and providing electrical stimulation for tissue treatment in vivo are discussed. Abstract : Recently, 1D nanomaterials are used in the field of bioelectronics for healthcare purpose. Although achieving perfect biocompatibility is very challenging, bioelectronics is developed for electrophysiological understanding that can modulate in‐vitro‐cultured cells as well as for therapeutic device that can manage disease through implantation. Along with biocompatibility issues, various 1D nanomaterial‐based bioelectronic applications are introduced.